Translations of Embedded Theorems in Z Specifications (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This paper discusses our proposal on how to embed theorems in Z specifications. One reason behind this proposal is to ease Z users in writing theorems directly in their Z specifications. Another reason is not to overwhelm Z users in learning other language, which in this case is SAL language. In doing so, we need to inform Z2SAL programmers how to translate these embedded theorems into equivalence theorems in SAL specifications. Based on our experiments, Z2SAL is able to translate these kind of theorems and SAL model checker is also able to model check SAL specifications with theorems that are written directly in the Z specifications.